Composition analysis and prebiotics properties of polysaccharides extracted from Lepista sordida submerged cultivation mycelium - Wang, Lanying; Lian, Junhui; Zheng, Qinhua; Wang, Liang; Wang, Yanzhen; Yang, Dongsheng (Frontiers in Microbiology, 2023)
In this paper, Lepista sordida polysaccharides (LSP) were separated from Lepista sordida（L. sordida） mainly using the Ultrasonic-Micro Wave Synergy Extraction (UMSE) method, the liquid is purified by graded alcohol precipitation to obtain three components: 40%LSPUMSE, 60%LSPUMSE, 80%LSPUMSE, and to explore the physicochemical properties, structural characteristics, antioxidant activity, and their effects on the proliferation of Lactobacillus casei of these three polysaccharides. By UV and FT-IR spectroscopy, all three polysaccharides showed characteristic absorption peaks at UV 200 nm. FTIR analysis showed that all three polysaccharides had β-glycosidic bond conformation, and the monosaccharides of 40%LSPUMSE, 60%LSPUMSE, and 80%LSPUMSE were mainly composed of glucose, mannose, galactose, and ribose. The antioxidant activity study revealed that the polysaccharides obtained by the UMSE method and after graded alcohol precipitation had better antioxidant activity compared to the traditional " Hot Water Extraction (HWE)" method. In addition, all graded alcoholic polysaccharides promoted the proliferation of L. casei to some extent. 40%LSPUMSE, 80%LSPUMSE had better acid production than inulin when verifying the carbon source, and all three LSPUMSE used as a carbon source for culturing L. casei significantly improved its tolerance to bile salts and promoted zwitterionic value when compared with glucose. The results of this study showed that the UMSE method significantly increased the antioxidant activity of LPS compared to the hot water extraction method, and LPSUMSE could be used as a potential prebiotic to promote the growth of probiotic bacteria.